IMPLEMENTASI SIMPLE NETWORK MANAGEMENT PROTOCOL (SNMP) PADA APLIKASI MONITORING JARINGAN BERBASIS WEBSITE(STUDI KASUS UNIVERSITAS MUHAMMADIYAH BENGKULU) - -, Diana; Maulana, Fadel (Jurnal Informatika, 2016)
Network management is the ability to monitor, control and planning a computer network and system components. Monitoring the network is part of network management. Simple Network Management Protocol (SNMP) is an application protocol on TCP / IP network that can be used for management and monitoring of computer network system. An application built with web-based will be able to provide advantages in ease of access, has a display in the form of a Graphical User Interface (GUI) to the administrator to read the conditions of a network of value provided by SNMP.The purpose of this study was to find a web-based monitoring system can be implemented using SNMP, as well as to determine the completion of the disruption of the network. From the research results can be shown that the monitoring system of web-based has been successfully implemented using the SNMP protocol as a data collection monitoring and database Round Robin (RRDtool) for the analysis of monitoring data and displays the data results of monitoring in the form of graphs and data obtained in the event of a network interruption enough accurate and sufficient information about the complete disruption.Keyword: network management,Simple Network Management Protocol(SNMP), website